PUBLIC PRIVATE PARTNERSHIP IN BUILDING RESEARCH FUNDING (Collaborative Study between the Indonesian Institute of Sciences and PT Dyandra Promosindo in Management Bogor Botanical Garden) - Ima Mayasari; Yavis Amanda (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
The problems in this study are focused on the collaboration between Indonesia Institute of Science (LIPI) and PT. Dyandra Promosindo as an alternative in research funding. The aim of this study was to analyze the partnership model carried out by LIPI with the private sector in the management of the Bogor Botanical Gardens using the Public Private Partnership (PPP) concept. The research approach used is a qualitative approach with reference to the theory of E. Savas (2000). The data were collected through a literature review (literature review) on the concept of public private partnership, reports on research budgeting, profiles of the Indonesian Institute of Sciences and Bogor Botanical Gardens as well as partnership agreements and were analyzed qualitatively. Then conducted interviews with Bogor Botanical Gardens managers, namely LIPI and Partners. The results of the study concluded that (1) In general, the collaboration is a PPP collaboration based on the dimensions of the roles and responsibilities of the government and the private sector, cooperation contracts entered into, transfer of duties and functions of services and risks, service managerial systems and service innovation by the private sector; (2) There are obstacles that affect the implementation of partnership cooperation.